Effect of Ethanol Extract of Date Palm Fruit (Phoenix dactylifera. L) on Spermatozoa Concentration of BALB/c Mice (Mus Musculus) Exposed to 2-Methoxyethanol - Yassin, Tita Rudini; Yaudiwati, Rina; I'tishom, Reny (Folia Medica Indonesiana, 2020)
Antioxidants are important compounds for the human body because they function to capture free radicals causing degenerative diseases. Flavonoid and phenolic compounds in dates have antioxidant activity that can inhibit the increase in lipid peroxide and protein oxide. This study aims to prove the increase in the concentration of mice (Mus musculus) spermatozoa given ethanol extract dates and exposed to 2-methoxyethanol. Experimental animals used 35 mice (Mus musculus), divided into 5 groups (7 mice per group). The negative control group (K-) was the control group without administration of 2-methoxyethanol and date ethanol extract, the positive control group (K+) was given 200 mg/kg 2-methoxyethanol + CMC 0.5%, the treatment group 1 (P1) was given 200 mg/kg BW 2-methoxyethanol + 3.5 mg/gBW of ethanol extract dates, treatment group 2 (P2) were given 200 mg/kg BW 2-methoxyethanol + 7 mg/gBW of date palm ethanol extract, and treatment group 3 (P3) were given 200 mg/kg 2-methoxyethanol + 10.5 mg/gBW of ethanol extract dates. The results showed there were significant differences in spermatozoa concentrations between the positive control group (K+) and the negative control group (K-), treatment group 1 (P1) and treatment groups 2 and 3. mice (Mus musculus) exposed to 2-methoxyethanol.